6 - Sustaining Global Skills Inequality? Skills Development and Skills Protectionism in the Nigerian Multinational Corporate Sector - Jiboku, Joseph O.; Akpan, Wilson (Africa Development, 2018)
The vital role of skills for socio-economic transformation is well espoused in the literature; however little scholarly attention has been paid to the international dichotomies in skills and the dynamics that underpin them. In many countries in the Global South, there is a plethora of liberal policies that seek to attract industrial investment by corporations in the Global North, the hope often being that the development of vital skills will result from such investments. Yet, studies have shown that in many developing countries, years of active business involvement by multinational corporations have not had the desired effects. Against this backdrop, this article examines the skills development programmes and strategies in Nigeria’s multinational corporate sector vis-à-vis the dominant national discourses on skills development in Nigeria. The focus is on the extent to which multinational corporations (MNCs) operating in Nigeria have facilitated the acquisition of vital skills. From interviews conducted in key Nigerian national manpower policy agencies and two multinational companies, with long active industrial operations in Nigeria, the article argues that despite their long existence, MNCs operating in Nigeria still source vital skills from their home countries. Besides, the levels of investment in skills development in the local economy suggest a possibility of skills protectionism – an active or unwitting process of ‘hoarding’ vital skills. The article thus highlights the challenges and contradictions of economic calculations of corporations and national human capital development imperatives.